Patients' perceptions of a culturally targeted Hispanic Kidney Transplant Program: A mixed methods study. Issue 6 (23rd May 2019) - Alhalel, Nathan; Francone, Nicolas O.; Salazar, Alice M.; Primeaux, Sharon; Ruiz, Richard; Caicedo, Juan Carlos; Gordon, Elisa J.
Abstract: Disproportionately fewer waitlisted Hispanics receive living donor kidney transplants (LDKTs) compared to non‐Hispanic whites. Northwestern Medicine's ® culturally targeted Hispanic Kidney Transplant Program (HKTP) is associated with a significant increase in LDKTs among Hispanics. This multisite study assessed potential kidney recipients' and donors' and/or family members' perceptions of the HKTP's cultural components through semi‐structured interviews and validated surveys. Qualitative thematic analysis and descriptive statistics were performed. Thirty‐six individuals participated (62% participation rate) comprising 21 potential recipients and 15 potential donors/family (mean age: 51 years, 50% female, 72% preferred Spanish). Participants felt confident about the educational information because a transplant physician delivered the education and viewed the group format as effective. Participants felt that education sessions addressed myths about transplantation shared by Hispanics. Primary use of Spanish enhanced participants' understanding of transplantation. While few knew about living donation before attending the HKTP, most were "more in favor of" kidney transplantation (97%) and living donation (97%) afterward. Few reported learning about the HKTP from outreach staff and suggested leveraging community leaders to promote HKTP awareness. Our findings suggest the HKTP's cultural components were viewed favorably and positively influenced perceptions of kidney transplantation and living donation, which may help reduce transplant disparities in Hispanics. (Clinicaltrial.gov registration # NCT03276390, date of registration: 9‐7‐17, retrospectively registered).